Mapping knowledge structure and themes trends in unilateral biportal endoscopic spine surgery: A bibliometric analysis - Zhu, Ming-Tao; Li, Kunrong; Hu, Bao-Shan; Chen, Chien-Min; Lin, Guang-Xun (Frontiers in Surgery, 2022)
Background: The numerous benefits of unilateral biportal endoscopic (UBE) spine surgery have attracted the attention of many researchers, and a considerable number of relevant clinical studies have been published. However, global research trends in the field of UBE have received little attention. The purpose of this study was to apply bibliometric method to analyze the UBE-related publications to obtain an overview of the research trends in the field of UBE, as well as research hotspots and trends. Methods: Web of Science database was searched for articles published until January 31, 2022. CiteSpace was used to analyze the data, which provided graphical knowledge maps. The following factors were applied to all literature: number of publications, distribution, h-index, institutions, journals, authors, and keywords. Results: Seventy-three articles were identified. Since 2019, there has been a significant increase in the number of UBE-related publications. The country with the largest number of articles was South Korea (72.6%), followed by China (9.6%), Japan (4.1%), and Egypt (4.1%). South Korea had the highest h-index (16), followed by China (2), Japan (1), and Egypt (1). Leon Wiltse Memorial Hospital was the organization that produced the most papers (12 publications). Heo DH was the most productive author (16 papers) and was the most cited author (35 times). World Neurosurgery published the most papers on UBE (23.3%). The main research hotspots were spinal diseases, decompression, complications, learning curve, and interbody fusion. In addition, the recent concerns were “learning curve,” “interbody fusion,” “management,” and “dural tear.” Conclusions: The quantity of publications on UBE research will increase, and South Korea being the major contributor and most prominent country in this field. The findings of our study will provide researchers with practical information on the field of UBE, and identification of mainstream research directions and recent hotspots.